Weighted Estimates for the Maximal Commutator of Singular Integral Operator on Spaces of Homogeneous Type (Communications in Mathematical Research, 2021)
Weighted estimates with general weights are established for the maximaloperator associated with the commutator generated by singular integral operator andBMO function on spaces of homogeneous type, where the associated kernel satisfiesthe Hölder condition on the first variable and some condition which is fairly weakerthan the Hölder condition on the second variable.
Keywords: spaces of homogeneous type; weighted estimates; singular integral operator; commutator; maximal operator.